2017
DOI: 10.1038/cmi.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs: novel regulators of autoimmunity-mediated pancreatic β-cell destruction in type 1 diabetes

Abstract: MicroRNAs (miRNAs) are a series of conserved, short, non-coding RNAs that modulate gene expression in a posttranscriptional manner. miRNAs are involved in almost every physiological and pathological process. Type 1 diabetes (T1D) is an autoimmune disease that is the result of selective destruction of pancreatic β-cells driven by the immune system. miRNAs are also important participants in T1D pathogenesis. Herein, we review the most recent data on the potential involvement of miRNAs in T1D. Specifically, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 114 publications
0
34
0
2
Order By: Relevance
“…Owing to their widespread distribution from prokaryotic to mammalian cells, it is not difficult to comprehend their extensive roles in maintaining cellular physiology and internal homeostasis [281]. With respect to the central nervous system, developmental researchers have identified that miRNAs are inevitable regulators during neurogenesis and maturity phase.…”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%
“…Owing to their widespread distribution from prokaryotic to mammalian cells, it is not difficult to comprehend their extensive roles in maintaining cellular physiology and internal homeostasis [281]. With respect to the central nervous system, developmental researchers have identified that miRNAs are inevitable regulators during neurogenesis and maturity phase.…”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%
“…Many experimental studies in cultured cells an d an imal models of T1DM have provided convincing evidence that miRNAs can participate in controlling β-cell fate, autoimmune damage of β-cells, an d regulation of insulin synthesis an d secretion [60]. In mice, the disruption of miR-155 promoted the onset of T1DM an d a reduction of Treg cell number [61].…”
Section: The Experimental Studies In Cultured Cells An D Animal Modelsmentioning
confidence: 99%
“…The evidence at this moment suggests that the transition into PILs is under post-transcriptional control exerted by miRNAs (Figure 1 ). Interestingly, some miRNAs such as miR-375, miR-30d and miR-9, can control insulin synthesis and secretion by pancreatic beta-cells ( 85 ) in NOD mice. Whether miRNAs also regulate the intrathymic production of proinsulin/insulin and IGF remains unknown.…”
Section: The Role Of Mirnas Throughout Transition Of Thymocytes Into mentioning
confidence: 99%